Role of Tissue Factor in the Coagulation Network - Cimmino, Giovanni; Ciccarelli, Giovanni; Golino, Paolo (Seminars in Thrombosis and Hemostasis, 2015)
It is generally accepted that the initial event in coagulation and intravascular thrombus formation is the exposure of the flowing blood to cell-surface protein, such as tissue factor (TF). Vascular injury and/or atherosclerotic plaque complication is responsible for this exposure, leading to clinical manifestations such as acute coronary syndromes. For many years, TF has been considered one of the major determinants of plaque-related thrombosis. However, the discoveries of different pools of TF that circulates in the blood as cell-associated TF, microparticles bound, and as soluble form have changed this dogma. Recent evidence suggests that an increased circulating TF activity may potentiate the initial thrombogenic stimulus related to vessel wall–associated TF, leading to the formation of larger and/or more stable thrombus and thus more severe clinical manifestations. Different pathological conditions, such as inflammatory status, enhance TF expression and activity. Conversely, TF upregulation may facilitate inflammation by formation of proinflammatory fibrin fragments and coagulation proteases generation, including FVIIa, FXa, and thrombin. Furthermore, the biology of TF has become more complex by the demonstration that, apart from its known effects on blood coagulation, it is involved in intracellular signaling, proliferation, angiogenesis, and tumor metastasis.
Keywords: coagulation cascade; tissue factor; thrombus formation; atherothrombosis